Special Issue “Microbial Endophytes: Functional Biology and Applications”: Editorial - Ajay Kumar; Gustavo Santoyo; James F. White; Virendra Kumar Mishra (Microorganisms, 2023)
Plants harbour various microbial communities, including bacteria, fungi, actinomycetes, and nematodes, inside or outside their tissues [...]